Analisis Hukum Kebijakan Lembaga Penjamin Simpanan (LPS) Mempertahankan Tingkat Bunga Penjaminan (TBP) Dalam Menjaga Stabilitas Perbankan - Eka Fadila Nur Faizah; Mario Paskalis Jegapu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Maintaining the Deposit Interest Rate (TBS) is one of the tasks of LPS in carrying out its functions, actively participating in maintaining the stability of the banking system in accordance with its authority, as intended in Article 4 letter a of the LPS Law. The deposit interest rate or savings interest rate (SBP) is the reward given by the bank to customers for the service of storing their money in the bank. Deposit interest rates are a form of bank appreciation for customers. Maintaining deposit interest rates can have a positive impact on banking stability in Indonesia.